Penerapan Studi Hadis Tematik di Bidang Politik dan Ketatanegaraan - Salsabila Itsnaini; Muhammad Alif; Hikmatul Luthfi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
The study of hadith in the contemporary era is not only limited to the theological dimension, but also extends to the socio-political and state realms. This is important to understand fair, inclusive governance based on Islamic values. In the context of modern Muslim countries, including Indonesia, the urgency to re-examine the function of hadith as a source of ethics and norms in politics is increasing, especially in facing the challenges of leadership and covering up power. This study aims to apply the thematic hadith approach (maudhu'i) in understanding contemporary political and state issues. The method used is qualitative literature study with a thematic approach, examining hadiths from authentic books such as Sahih Bukhari, Muslim, and Abu Dawud, as well as classical literature and accredited scientific journals. The results of the study show that thematic hadiths provide a strong ethical and normative framework for the formation of a government system that is oriented towards justice, deliberation, and the responsibility of leaders. Hadith is also the basis for legitimizing criticism of authoritarian power, relevant to be implemented in democratic systems in Muslim-majority countries. Thus, the integration of hadith in contemporary political discourse is not merely idealistic, but has an epistemic basis that can be realized institutionally.